Is it possible to use riamilovir to prevent infection and treat COVID-19? - V. M. Tsvetov; K. B. Mirzaev; D. A. Sychev (Izdatelstvo OKI, 2020)
Routine clinical use of riamilovir in COVID-19 is not recommended. The use of riamilovir is possible in clinical trials.